2022
DOI: 10.3389/fendo.2022.813320
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Mutation of gsdf Causes Infertility in Female Nile Tilapia (Oreochromis niloticus)

Abstract: Gonadal somatic cell-derived factor (Gsdf) is a member of the TGF-β superfamily, which exists mainly in fishes. Homozygous gsdf mutations in Japanese medaka and zebrafish resulted in infertile females, and the reasons for their infertility remain unknown. This study presents functional studies of Gsdf in ovary development using CRISPR/Cas9 in Nile tilapia (Oreochromis niloticus). The XX wild type (WT) female fish regularly reproduced from 12 months after hatching (mah), while the XX gsdf-/- female fish never r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(107 reference statements)
2
4
0
Order By: Relevance
“…Alternatively, in the XX spotted scat, despite the high level of gsdf expression, it could not induce the testicular differentiation for lack of intact dmrt1 (Mustapha et al, 2018). The present results support our previous conclusion that gsdf acts as a downstream gene of dmrt1 in testicular differentiation in fish (Jiang et al, 2016;Jiang et al, 2019;Jiang et al, 2022) (Figure 7). The spotted scat with male-specific dmrt1 as the candidate sex determination gene is a special model to study genes involved in sex differentiation.…”
Section: The Critical Genes In the Male Differentiation Pathwaysupporting
confidence: 88%
See 1 more Smart Citation
“…Alternatively, in the XX spotted scat, despite the high level of gsdf expression, it could not induce the testicular differentiation for lack of intact dmrt1 (Mustapha et al, 2018). The present results support our previous conclusion that gsdf acts as a downstream gene of dmrt1 in testicular differentiation in fish (Jiang et al, 2016;Jiang et al, 2019;Jiang et al, 2022) (Figure 7). The spotted scat with male-specific dmrt1 as the candidate sex determination gene is a special model to study genes involved in sex differentiation.…”
Section: The Critical Genes In the Male Differentiation Pathwaysupporting
confidence: 88%
“…In this study, gsdf is highly expressed in the testes similar to the results in the adult spotted scat (He et al, 2019;Jiang et al, 2019;Mustapha et al, 2021). In Nile tilapia, Yeast-two-hybrid assays showed that amhr2 and bmpr2a might be the type II receptors of gsdf (Jiang et al, 2022).…”
Section: The Critical Genes In the Male Differentiation Pathwaysupporting
confidence: 85%
“…Support cells (granulosa cells in the ovary and Sertoli cells in the testis) control germ cell proliferation, differentiation, and maturation. Support cells in fish express gsdf both in ovaries and in testes and gsdf is required for oocyte maturation ( Sawatari et al, 2007 ; Gautier et al, 2011 ; Imai et al, 2015 ; Zhang et al, 2016 ; Yan et al, 2017 ; Jiang et al, 2022 ). Furthermore, a variant of gsdf is the major male sex determining gene in Luzon medaka and sablefish ( Myosho et al, 2012 ; Herpin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Support cells -- granulosa cells in the ovary and Sertoli cells in the testis -- control germ cell proliferation, differentiation, and maturation. Support cells in fish express gsdf in both ovaries and testes and gsdf is required for oocyte maturation (Sawatari et al, 2007, Gautier et al, 2011, Imai et al, 2015, Zhang et al, 2016, Yan et al, 2017, Jiang et al, 2022). Furthermore, a variant of gsdf is the major male sex determining gene in Luzon medaka and sablefish (Myosho et al, 2012, Herpin et al, 2021).…”
Section: Resultsmentioning
confidence: 99%